Novel Hybrids of Podophyllotoxin and Coumarin Inhibit the Growth and Migration of Human Oral Squamous Carcinoma Cells - Bai, Guohui; Zhao, Dan; Ran, Xin; Zhang, Lei; Zhao, Degang (Frontiers in Chemistry, 2021)
Oral squamous cell carcinoma is the most common malignancy of oral tumor. In this study, two novel hybrids of podophyllotoxin and coumarin were designed using molecular hybridization strategy and synthesized. Pharmacological evaluation showed that the potent compound 12b inhibited the proliferation of three human oral squamous carcinoma cell lines with nanomolar IC50 values, as well as displayed less toxicity on normal cells. Mechanistic studies indicated that 12b triggered HSC-2 cell apoptosis, induced cell cycle arrest and inhibited cell migration. Moreover, 12b could disturb the microtubule network via binding into the tubulin. It was noteworthy that induction of autophagy by 12b was associated with the upregulation of Beclin1, as well as LC3-II. Furthermore, 12b significantly stimulated the AMPK pathway, and restrained the AKT/mTOR pathway in HSC-2 cells. These results indicated that compound 12b was a promising candidate for further investigation.